Prevalence and Impact of Vitamin D Deficiency Among Individuals Diagnosed with Chronic Liver Disease - Naeem Ullah, Hina Shaukat, Syed Abdullah, Nisar Ahmed Khan, Akhtar Zada, Fida Muhammad Khan, Muhammad Younas, Subhan Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Chronic liver disease is characterized by multi-nutrient deficiency. The propensity for individuals to have vitamin D insufficiency is greater in comparison to other essential minerals. Fibrosis results in a decline in the liver’s ability to perform synthetic functions ultimately leading to lack of vitamin D due to poor activation caused by drop in proteins binding the vitamin. The situation is exacerbated by the decrease in productivity and the presence of nutritional deficiencies. Materials and Methods: The present descriptive research was carried out in the Department of Medicine at DHQ Teaching Hospital Haripur spanning from 1st January 2022 to 31st December 2022. The study population consisted of individuals between the ages of 40 and 70 years who were diagnosed with chronic liver disease. The concentration of vitamin D was assessed in blood samples obtained from patients at the hospital laboratory. The established threshold for identifying vitamin D insufficiency is a blood vitamin D level below 30 nmol/L. Data analysis was performed using statistical software SPSS version 24. Results: The age of the patients ranged from 40 to 70 years. The mean age of the patients was 53.40 years with standard deviation 12.194. Age wise distribution revealed 60.1% patients (n = 89) in the age group 40-55 years and 39.9% participants (n = 59) had age 56-70 years. The number of male participants were 94 (63.5%). Vitamin deficiency was observed in 64.9% patients (n = 96). The association of vitamin D deficiency with disease duration, child class and gender were statistically significant (p < 0.05). Conclusion: The potential association between vitamin D insufficiency and the extent of liver function impairment, degree of fibrosis, and susceptibility to infection consequences suggests that it may serve as a valuable prognostic indicator and diagnostic tool. Additional research is required to thoroughly assess and substantiate the significance of vitamin D in the context of liver cirrhosis. This necessitates the undertaking of extensive prospective cohort studies and randomized trials. Keywords: Vitamin D deficiency, Chronic Liver Disease (CLD)